Investment facilitation: new dynamism at the WTO on investment - Reji K. Joseph (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
The proposal for an investment facilitation agreement has brought about a new dynamism on investment issues at the WTO. Unlike in the past, it is the developing countries and least developed countries who champion the discussions. They hold that trade and investment policies are inseparable.
Keywords: 330